Distribution of mercury content in topsoil of coal base, Wuda, China - Cao Qingyi; Liang Handong; Chen Yang; Li Zhiwei; Liu Hongwei (矿业科学学报, 2018)
232 topsoil samples covering were collected from 200 km2 in Wuda area of Wuhai city, Inner Mongolia.The mercury content of topsoil was measured by Lumex RA-915.The results showed that the average mercury content of topsoil in the coalfield, industrial park, urban area, farm and peripheral area were 210 ng/g, 200 ng/g, 76 ng/g, 62 ng/g and 42 ng/g, respectively.Compared with the mercury background value of the topsoil in Wuda and the moisture soil in China, the mercury content of the topsoil in coalfield and industrial park was obviously enriched.Mercury enrichment of topsoil in coalfield was majorly caused by spontaneous combustion of underground coal seams and surface gangue.The desert in the northwestern had a dilution effect on the mercury concentration in topsoil of the coalfield, and the dilution strength increased along the wind direction.Atmospheric mercury released from industrial point sources such as coal-electricity, chlor-alkali industries was the main controlling factor of affecting the surface mercury distribution in industrial park.The relative high mercury content area of topsoil in urban and farm was mostly concentrated in the transition zones with coalfield and industrial park.By the evaluation of geo-accumulation index Muller, the results showed that 19% of the coalfield reached the level of moderate and above pollution, and 2% area was close to heavy pollution.Industrial park in the middle and above pollution was accounted for 18%, 7% area was close to heavy pollution, and heavy pollution was accounted for 2%.Urban, farm and peripheral area were found less plhuted.